2023
DOI: 10.1523/eneuro.0177-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Visual Contrast Sensitivity with tRNS across the Visual System, Evidence from Stimulation and Simulation

Abstract: Transcranial random noise stimulation (tRNS) has been shown to significantly improve visual perception. Previous studies demonstrated that tRNS delivered over cortical areas acutely enhances visual contrast detection of weak stimuli. However, it is currently unknown whether tRNS-induced signal enhancement could be achieved within different neural substrates along the retino-cortical pathway.In 3 experimental sessions, we tested whether tRNS applied to the primary visual cortex(V1) and/or to the retina improves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…The required sample size was estimated using an a priori power analysis [G*Power version 3.1 ( 49 )] based on the effect of maximum contrast sensitivity improvement with tRNS shown by Potok et al ( 50 ) ( = 0.165, effect size f = 0.445). It revealed that 28 participants should be included in an experiment to detect an effect with repeated-measures analysis of variance (rmANOVA, 4 levels of stimulation condition), α = 0.05, and 90% power.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The required sample size was estimated using an a priori power analysis [G*Power version 3.1 ( 49 )] based on the effect of maximum contrast sensitivity improvement with tRNS shown by Potok et al ( 50 ) ( = 0.165, effect size f = 0.445). It revealed that 28 participants should be included in an experiment to detect an effect with repeated-measures analysis of variance (rmANOVA, 4 levels of stimulation condition), α = 0.05, and 90% power.…”
Section: Methodsmentioning
confidence: 99%
“…In each experiment, three tACS intensities and a control no tACS condition were interleaved in random order. Our main outcome parameter in all experiments was a threshold of visual contrast detection (VCT) that was determined for each of the different tACS conditions ( 50 ). The experimental procedure to estimate VCT followed a previously used protocol to assess the influence of tRNS on contrast sensitivity ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations